Strengthening the Integrity of Local Leadership and its Relevance to Run Democratic Governance - Maulana Mukhlis; Idil Akbar (Universitas Lampung, 2017)
AbstractEven though many aspects that show the way to run a democratic government, but the most important aspect is related to the leadership of integrity. The leadership of integrity put the perspective of power in the orientation of partisanship on the people. Also, democratic governance at the local level can be run effectively and constructively if the leadership held with integrity. In another word, the leadership of integrity is a requirement to run a democratic government. Therefore, the integrity of local leadership should be encouraged. Strengthening the integrity of local leadership includes two main things, namely giving a great opportunity for people participation and is committed to a clean and accountable government. Our conception of the strengthening the local leadership integrity and relevance of a democratic government explains important aspects of leadership in maintaining the continuity of a government. For success or failure of a reign depends on how to reach a democratic government that can be reached and gets the highest appreciation from the community. Therefore, the purpose of the writing of this article is to explain the significance between the leadership of integrity with democratic governance and elaborating how to strengthen the integrity of the leadership in the efforts to reach a democratic government. Keywords: Leadership, Leadership Integrity, Democracy, Local Government, Democratic Governance.